Knowledge, attitude & practice of self-medication with painkillers among young adults, Bangladesh - Sarker, Rumpa; Moonajilin, M Sabrina (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Self-medication, the unsolicited use of prescription and over the counter (OTC) drugs, is practised all over the world, particularly in countries like Bangladesh. So, this study is focused on the prevalence and attitude and knowledge about various aspects of self-medication with painkillers among students of the selected residential university of Dhaka, Bangladesh. Methods It is a cross-sectional interview-based study. The study population was the students of the university who lives in attached residential halls. The total number of respondents was 209. Results Every respondent both male (105) and female (104) have reported that they had practiced self-medication with painkillers for their both acute and chronic pain like headache, menstrual cramp, back/muscle/joint pain etc. Drugs commonly used by the students were Napa (19.6%), Paracetamol (12.9%), Etorix (6.2%), ACE (10.0%) HPR ds (10.0%), Rolac (9.6%) etc. Many of the drugs were non-OTC drugs. The main sources of information were advised by the manager of the pharmacy (36.8%), self-decision (16.7%), media (12.0%) and advice from friends/relatives (23.0%). The prime factors that influenced students to try self -medicated painkillers were dissatisfaction toward the medical centre in the area (23.9%), cost-effectiveness (20.6%), unavailability of medical facilities (11.5%) etc. 64 of the respondents (both M & F) reported that they have no clear idea about the possible side effects of the chronic use of painkillers. Dependency on a painkiller for pain management was (M=32 and F=48). Conclusions 41% of students taking a self-medicated painkiller with analgesics in an emergency perceive it as safe.